2007
DOI: 10.1117/1.2772296
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive biosensor array using surface plasmon resonance on metallic nanoslits

Abstract: Chip-based biosensor arrays for label-free and high-throughput detection were fabricated and tested. The sensor array was composed of a 150-nm-thick, 50-nm-gap, and 600-nm-period gold nanoslits. Each array size was 100 mumx100 mum. A transverse-magnetic polarized wave in these metallic nanostructures generated resonant surface plasmons at a wavelength of about 800 nm in a water environment. Using the resonant wavelength shift in the nanoslit array, we achieved detection sensitivity up to 668 nm per refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(64 citation statements)
references
References 15 publications
3
61
0
Order By: Relevance
“…Tens of thousands of SPR detection points can be put on a glass slide. Therefore, periodic metallic nanostructures are very suitable for high-throughput and chip-based detections [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Tens of thousands of SPR detection points can be put on a glass slide. Therefore, periodic metallic nanostructures are very suitable for high-throughput and chip-based detections [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Recently, periodic gold nanohole arrays or nanoslit arrays have been utilized for biosensing applications. [8][9][10][11][12][13][14][15][16][17][18][19] By measuring changes in the resonant angle, wavelength or intensity, the amounts of surface binding events are quantitatively estimated. The detection limit of the SPR sensor is usually characterized by minimum refractive index unit (RIU).…”
Section: Doi: 101002/adma201202194mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Applications of devices containing nanoslit structures include biosensors, 5,14 terahertz antennas, 9 and lenses with controllable parameters. [15][16][17][18] Experimental and theoretical research has confirmed that not only can these nanostructures enhance an incident electric field, but also the nanogaps that separate them can provide additional enhancement.…”
Section: Introductionmentioning
confidence: 99%